2010
DOI: 10.1038/ncb2103
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells dynamically compete for the tip cell position during angiogenic sprouting

Abstract: Sprouting angiogenesis requires the coordinated behaviour of endothelial cells, regulated by Notch and vascular endothelial growth factor receptor (VEGFR) signalling. Here, we use computational modelling and genetic mosaic sprouting assays in vitro and in vivo to investigate the regulation and dynamics of endothelial cells during tip cell selection. We find that endothelial cells compete for the tip cell position through relative levels of Vegfr1 and Vegfr2, demonstrating a biological role for differential Veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

59
922
5
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 857 publications
(1,012 citation statements)
references
References 47 publications
59
922
5
12
Order By: Relevance
“…Recently, it has been shown that VEGFR1 and VEGFR2 reciprocally determine tip cell selection. For the initiation of the sprouting process, the cell needs lower VEGFR1 and higher VEGFR2 levels, where the latter is involved in negative feedback with Notch [4]. It is plausible to expect that with increase in the ratio VEGFR2/ VEGFR1, there will be enhanced sprouting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that VEGFR1 and VEGFR2 reciprocally determine tip cell selection. For the initiation of the sprouting process, the cell needs lower VEGFR1 and higher VEGFR2 levels, where the latter is involved in negative feedback with Notch [4]. It is plausible to expect that with increase in the ratio VEGFR2/ VEGFR1, there will be enhanced sprouting.…”
Section: Discussionmentioning
confidence: 99%
“…Gerhardt et al demonstrated that during sprouting angiogenesis, endothelial cells compete for the leading tip position, and it is dependent not on the absolute but on the relative VEGFR levels between cells. The cells expressing less VEGFR1 or more VEGFR2 have high probability to be found at the tip position, and VEGFR level-mediated competition is strictly Notch dependent [4]. In addition to negative effects on sprouting, Notch signaling has also been shown to have effects on stabilization of vasculature and vessel remodeling [15][16][17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial cells of Drosophila tracheal branches undergo extensive rearrangement (2), requiring remodeling of adherens junctions (3). Similarly, mural endothelial cells (ECs) 5 move extensively during intersegmental vessel (ISV) sprouting in the zebrafish (4,5), during the expansion of the retinal vasculature in the mouse, and during vessel sprouting from embryoid bodies (5). Junction remodeling between epithelial and ECs requires endocytosis and trafficking of junction transmembrane proteins (6).…”
mentioning
confidence: 99%
“…Chez l'adulte, mécanisme permet que seule la cellule de front, qui exprime fortement VEGF-R2 et la protéine DLL4, puisse répondre au signal pro-angiogénique induit par le VEGF. De manière intéressante, cette compétition de signalisation (DLL4 versus VEGF), et donc de positionnement de la cellule de front, pourrait assurer une sélection continue durant l'allongement du vaisseau et inté-grer d'autres signaux morphogénétiques tels que ceux induits par les BMP responsables de la quiescence des cellules [5]. SYNTHÈSE REVUES le modèle du poisson zèbre, l'analyse des vaisseaux intersomitiques montre que ces filopodes sont impliqués dans la vitesse de migration mais qu'ils ne participent pas à l'orientation de la cellule [7].…”
Section: L'angiogenèse : Une Valse à Quatre Tempsunclassified